Implementation of the breadth-first search method on forward-chaining inferences to diagnose autism disorders in children - Dodi Nofri Yoliadi (Institute of Computer Science (IOCS), 2023)
Autism is a type of mental disorder that can affect children as young as three years old, but can affect children from birth. This mental disorder is characterized by social relationships, culture, verbal and non-verbal communication, imagination, and a single attractive object. By using the Autism Disorder Diagnostic Expert System, we hope that most people will be able to attempt an autism diagnosis without an expert. This system works by answering all system questions. The